Students' Agentic Engagement Predicts Longitudinal Increases in Perceived Autonomy-Supportive Teaching: The Squeaky Wheel Gets the Grease. Issue 4 (2nd October 2018) - Matos, Lennia; Reeve, Johnmarshall; Herrera, Dora; Claux, Mary
ABSTRACT: Recognizing that teachers' motivating styles predict students' classroom engagement, we investigated whether students' classroom engagement might predict a change in teachers' motivating styles, though we investigated only students' perceptions of these changes. Using a self-determination theory framework and a classroom-based longitudinal research design, 336 Peruvian university students self-reported their teachers' perceived autonomy-supportive teaching and four aspects of their own engagement (behavioral, emotional, agentic, and cognitive) at the beginning (T1) and end (T2) of a semester. As expected, earlysemester perceived autonomy-supportive teaching predicted longitudinal increases in all four aspects of students' late-semester engagement. More importantly, students' early-semester agentic engagement predicted longitudinal increases in perceived autonomy-supportive teaching, which suggests that students' classroom engagement may recruit greater perceived autonomy support.